KONSTRUKSI PEMAKNAAN SIMBOLIS SALAMAN MENCIUM TELAPAK DAN PUNGGUNG TANGAN GURU OLEH SANTRI PONPES NURUL YAQIN - Ade Dasrial; Sarmiati Sarmiati; Afrizal Afrizal; Zainal Zainal (Universitas Islam Negeri Imam Bonjol Padang, 2020)
This research is about hand-kissing behavior done by santri, students at traditional Muslim school, towards their teachers in Nurul Yaqin Islamic boarding school. Nurul Yaqin's santri-style greetings have their meanings. Researchers focus on discussing the ways, meanings and meanings construction process in the hand-kissing behavior. This study aims to investigate how santri do hand-kissing in detail to their teachers, as well as examine more deeply the meaning and meaning construction process of the symbolic behavior of hand-kissing. This study uses qualitative research methods with a phenomenological approach. The results showed that the hand-kissing was done by kissing the back of the hand, then inverted to then kiss the palm, the kiss is inhaled using the nose. The meaning of the hand-kissing is a symbol of the blessing of zahir and inner knowledge obtained from the teachers to Allah SWT. The construction process of meaning starts from the beginning of the santri entering the cottage. At that time the students had their own meaning to the behavior of the hands-kissing. After some time, the meanings are equated with the meanings given by Shaykh al-Ma'ad. This process of equating meaning is done by asking directly to Shaykh al-Ma'ad, their teachers and seniors.